Inclusive Training in Kapalo Panitik Embroidery for People with Disabilities as an Effort to Preserve Local Culture in Pariaman - Ananda Putriani; Nanda Rian Putra; Nur Indah Yusari; Dewi Sari Sumitro; Dian Arsa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Kapalo Panitik embroidery in Nareh is a local cultural heritage of the Pariaman community that embodies the aesthetic values and cultural identity of the Minangkabau people. However, this traditional embroidery is facing challenges due to a lack of new artisans and low community involvement in preserving local culture, including among people with disabilities. This community service initiative aims to enhance the skills of people with disabilities in the field of Kapalo Panitik embroidery while supporting the preservation of local culture in Pariaman through an inclusive and participatory training approach. The program was implemented through hands-on training (learning by doing), comprising preparation, training, mentoring, evaluation, documentation, and dissemination phases. The activity was carried out in 16 training sessions involving 12 people with physical disabilities in the city of Pariaman. The results of the activity showed an improvement in participants’ skills in understanding basic embroidery techniques, an increase in the neatness of their work, as well as an increase in participants’ self-confidence and social participation in cultural activities. In addition to producing embroidered products and uncang, this activity also produced a documentary video and a digital catalog as a form of documentation and preservation of the Sulaman Nareh culture. This training program demonstrates that local culture can serve as a medium for social empowerment and the strengthening of cultural literacy for people with disabilities through an inclusive and sustainable cultural approach.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//